《素問·氣府論》에 대한 연구 - 오이수(Yi Soo Oh); 김보훈(Bo Hun Kim); 노승조(Seung Jo Roh); 천상묵(Sang Muk Cheon); 김종호(Jong Ho Kim); 정현종(Hyun Jong Jeong); 이종순(Jong Soon Lee); 정헌영(Heon Young Jeong); 금경수(Kyung Soo Keum) (동의생리병리학회지, 2004)
This paper discuss the acupoints and flowing of channel. The Acupoints issued from the Foot Taiyin channel's energy are seventy three. The acupoints issued from the Foot Shaoyang channel's energy are sixty two. The acupoints issued from the Foot Yangming channel's energy are sixty eight. The acupoints issued from the Hand Taiyang channel's energy are thirty six. The acupoints issued from the Hand Yangming channel's energy are twenty two. The acupoints issued from the Hand Shaoyang channel's energy are thirty two. The acupoints issued from the Du channel's energy are twenty eight. The acupoints issued from the Ren channel's energy are twenty eight. The acupoints issued from the Chong channel's energy are twenty two. The acupoints issued from the Foot Shaoyin channel are the Lianquan points of kidney channel on each side under the tongue. The total points above amount of three hundred and sixty five. Urinary Bladder Channel of Foot-Taiyang: The number of acupoints is 67. Gall Bladder Channel of Foot-Shaoyang: The number of acupoints is 44. Stomach Channel of Foot-Yangming: The number of acupoints is 45. KCI Citation Count: 0